International Law and Struggle for the Freedom and Welfare of Man in Africa - Sagay, Itsejuwa E. (Obafemi Awolowo University Press, 2013)
In this lecture, I intend to examine very briefly, the status of Human Rights in International Law, and its state within the independent countries of Africa, including intra-African practice in this vital aspect of human existence. My personal contribution to knowledge in this area will not receive much consideration since my primary aim is not only to explain and enlighten, but also, and this in my view is the most important, to create greater awareness of the gross inadequacies in the implementation of Human Rights obligations in Africa and generate some momentum towards the effective promotion and protection of Human Rights in the continent.